Program Konseling Karir “Man Jadda Wajada” Untuk Meningkatkan Kemampuan Penetapan Keputusan Karir Pada Remaja SMA di Panti Asuhan - Eka Fitriyani; Rita Susanti (Lembaga penelitian dan pengabdian kepada masyrakat, 2022)
Orphanage youth generally have difficulty in determining academic or occupational majors, when they are able to decide, the problem that arises is not understanding enough of the choices that have been made Career counseling is a means that can play a role in ensuring individuals make career decisions, and help fulfill the requirements that must be met. possessed in fulfilling career development tasks. Career counseling services are one of the areas of guidance that try to help individuals in solving career or work problems to adjust as well as possible for their future. This service is a continuation of the future orientation training program in the field of work for adolescents at the Pekanbaru orphanage. Career counseling services are provided to high school students who live in orphanages. The number of participants in this service is 11 teenagers. The results of the analysis of the difference test before and after on the ability to determine career decisions show a Z value of 2.666 with a significance of 0.008 (p <0.05), meaning that there is a change in the ability to make career decisions before and after giving career counseling.